Confiscation of Assets Laundered through Cryptocurrency Transactions in Indonesia: A Regulatory Framework - Mahdavika Arsy Mubarak; Ayu Izza Elvany (Contemporary Issues in Criminal Law, 2024)
The newly emerged method of Money Laundering (ML) is to purchase cryptocurrency. The anonymity of cryptocurrency makes it difficult to identify perpetrators for the purpose of asset confiscation. Unfortunately, Indonesia does not have the law on asset confiscation. This research analyses the legislation on asset confiscation in case of ML through cryptocurrency transactions in Indonesia and the extent of the Asset Confiscation Bill in covering asset confiscation from ML through cryptocurrency transactions. This doctrinal legal research uses both statutory and conceptual approaches to address the proposed legal issues. The results of this study indicate that the regulation of asset confiscation in the Money Laundering Act in Indonesia still places the criminal confiscation to certain goods as an additional punishment that must be imposed along with the primary punishment, making it difficult to reach the asset confiscationof ML through cryptocurrency transactions. Furthermore, the concept of following the money in the Asset Confiscation Bill reaches the nominee mode. Asset confiscation is carried out without criminal conviction by proving that the assets were indeed derived from criminal proceedings, which is sufficient for submitting an application for asset confiscation. The Bill does not address the problem when the arrangement uses the DEX model as the issue lies in the technical execution. Hence, specific regulations and procedural law are needed to confiscate assets that have been laundered through cryptocurrency transactions as well as to synergise the dynamics between the law enforcement and the suspect in order to successfully confiscate the said assets. Keywords: Asset Forfeiture, Cryptocurrency, Legislation, Money Laundering. Abstrak Metode baru Pencucian Uang (ML) adalah membeli cryptocurrency. Anonimitas cryptocurrency membuat sulit untuk mengidentifikasi pelaku penyitaan aset. Sayangnya, Indonesia tidak memiliki undang-undang penyitaan aset. Penelitian ini menganalisis peraturan perundang-undangan penyitaan aset ML melalui cryptocurrency di Indonesia dan sejauh mana RUU Perampasan Aset dalam mencakup penyitaan aset dari ML melalui cryptocurrency. Penelitian hukum doktrinal ini menggunakan pendekatan hukum dan konseptual untuk mengatasi masalah hukum yang diusulkan. Hasil penelitian ini menunjukkan bahwa pengaturan penyitaan aset dalam Undang-Undang Tindak Pidana Pencucian Uang di Indonesia masih menempatkan penyitaan pidana terhadap barang-barang tertentu sebagai hukuman tambahan yang harus dijatuhkan bersamaan dengan hukuman utama, sehingga sulit untuk mencapai penyitaan aset ML melalui Cryptocurrency. Selanjutnya, konsep follow the money dalam RUU Perampasan Aset mencapai mode nominee. Penyitaan harta dilakukan tanpa pemidanaan pidana dengan membuktikan bahwa harta kekayaan tersebut berasal dari hasil tindak pidana, yang cukup untuk mengajukan permohonan penyitaan harta benda. Bill tidak menjawab masalah ketika penempatan menggunakan model DEX karena masalahnya ada pada eksekusi teknis. Oleh karena itu, peraturan khusus dan hukum acara diperlukan untuk menyita aset yang dicuci uang melalui cryptocurrency. Kata kunci: Perampasan Aset, Cryptocurrency, Legislasi, Pencucian Uang.